Post-narratology through computational and cognitive approaches - Ogata, Takashi, 1958-; Akimoto, Taisuke, 1984- (Information Science Reference, 2019)
"This book discusses issues of narrative-related information and communication technologies, cognitive mechanism and analyses, and theoretical perspectives on narratives and the story generation process. Focusing on emerging research as well as applications in a variety of fields including marketing, philosophy, psychology, art, and literature"--